(untitled) (LEGAL DIALOGICA, 2025)
This research aims to know and understand the practice of judicial activism by the Constitutional Court (MK) in Indonesia in an essential way and the legitimacy of this practice. This writing uses Normative legal research methods sourced from primary legal materials and secondary legal materials, primary legal materials, namely legal materials sourced from the Holy Scriptures and legal materials sourced from laws and regulations, and also legal materials that have binding force in general and secondary legal materials, namely various references or scientific works in the field of law, in the form of legal books, legal articles, legal journals and academic papers in the field of law, legal texts from workshops and so on, and also legal materials that provide explanations for primary legal materials taken from several expert views related to this writing. The results showed that the development of existing law in Indonesia is a necessity, one of which is in the field of constitutional justice (Constitutional Court) which in its development can be more adaptive, progressive to uphold the constitution, protect the constitutional rights of citizens and oversee policies to be in accordance with its corridors, even though the path taken uses the practice of judicial activism. Writing recommendations: (1) The government and society should continue to supervise and oversee the practice of judicial activism so that it is directed to its corridors and prevent abuse of power. (2) The government and policy makers in this case can be more adaptive in revitalizing and strengthening the system and the rule of law in order to support a more directed and legitimate practice of judicial activism. Abstrak: Penelitian ini bertujuan untuk mengetahui dan memahami praktik judicial activism oleh Mahkamah Konstitusi (MK) di Indonesia secara eksiatensial dan legitimasi praktik tersebut.Penulisan ini menggunakan metode penelitian hukum Normatif yang bersumber dari bahan hukum primer dan bahan hukum sekunder, bahan hukum primer yaitu bahan hukum yang bersumber dari Kitab Suci maupun bahan hukum yang bersumber dari peraturan perundang-undangan, dan juga bahan hukum yang mempunyai kekuatan mengikat secara umum dan bahan hukum sekunder yaitu berbagai referensi atau karya-karya ilmiah bidang hukum, berupa buku hukum, artikel hukum, jurnal hukum dan naskah-naskah akademik bidang hukum, naskah hukum hasil lokakarya dan sebagainya, dan juga bahan hukum yang memberi penjelasan terhadap bahan hukum primer yang diambil dari beberapa pandangan ahli yang berkaitan dengan penulisan ini.Hasil penelitian menunjukkan bahwa perkembangan hukum yang ada di Indonesia merupakan keniscayaan, salah satunya ada pada bidang peradilan konstitusi (Mahkamah Konstitusi) yang dalam perkembangannya dapat lebih adaptif, progresif untuk menegakkan konstitusi, melindungi hak konstitusional warga negara dan mengawal kebijakan agar sesuai pada koridornya, walaupun jalan yang ditempuh menggunakan praktik judicial activism.Rekomendasi penulisan : (1) Pemerintah dan masyarakat terus mengawasi dan mengawal praktik judicial activism agar terarah pada koridornya dan mencagah adanya penyalahgunaan kekuasaan. (2) Pemerintah maupun pemangku kebijakan dalam hal ini dapat lebih adaptif dalam merevitalisasi dan memperkuat sistem maupun aturan hukum demi menunjang praktik judicial activism yang lebih terarah dan legitimate.